Temporarily blocking of bone growth areas for the correction of angular epimetaphyseal deformities of the knee joint in children - Korzh, Mykola; Khmyzov, Sergey; Korolkov, Oleksandr; Iershov, Dmytro; Pashenko, Andrey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Objective: To present outcomes of applying of a method of temporary blocking of long bones’ sprout area for treatment of frontal angular knee joint deformities (FAKJD) in children. Methods: From 2010 to 2014 at the clinic of the Institute we treated 14 patients (9 boys, 5 girls) with FAKJD (mean age 11 years 2 months). In 8 patients (57.1 %) we revealed varus, and in 6 (42.85 %) valgus deformity. Among children with varus FAKJD in 7 of them we diagnosed Erlacher-Blount disease, and in 1 we found postosteomyelitic deformation. In patients with valgus FAKJD in 5 cases we revealed dysplastic deformities, and in 1 — postosteomyelitic deformation. We performed clinical examination with measurement of tibial-femoral angle (TFA) and X-ray protocol proposed by D. Paley. The average value of clinical TFA in patients with varus FAKJD was 15° (10° to 24°), and with valgus — 13,25° (11° to 18°). In all patients we performed temporary blocking of long bones’ sprout area using the plate with two screws. Control examinations were performed every 3 months. We defined clinical TFA, radiological assessment of deformation conducted according to D. Paley. After reaching full correction of deformity we removed plates. Results: Full correction of FAKJD in 13 patients there was in a period of 7 to 16 months. In one child with varus FAKJD (age 10 years) correction for 14 months could not be reached because of the lack of growth of the patient. The average speed of correction of deformation was 0,9° per month. Complications during treatment were not recorded. Conclusions: Minimally invasive method presented is effective in treating FAKJD in children with Erlacher-Blount disease, and with deformities of dysplastic and postosteomyelitic etiology.